Age and origin of Late Quaternary eolianite, Kaiehu Point (Moomomi), Molokai, Hawaii - Fletcher, C. H.; Murray-Wallace, C. V.; Glenn, C. R.; Sherman, C. E.; Popp, B.; Hessler, A. (Journal of Coastal Research, 2005)
A well-preserved, vertically stacked succession of two genetically distinct eolianites and associated caliche paleosol units, capped by modern and Holocene coastal dunes, occurs at Kaiehu Point, west Molokai, Hawaii. The Pleistocene eolianite facies comprise well-cemented, medium grained skeletal carbonate sand and their morphostratigraphic context implies formation at times of lower than present sea level. Amino acid racernization (AAR) evidence suggests eolianite formation late in marine Oxygen Isotope Stage (OIS) 5, but lacks the precision to uniquely define in which isotopic substage the deposits formed. Coupled with the AAR results, the morphostratigraphic evidence, would suggest that the Lower Eolianite formed in OIS 5c and the Middle Eolianite during 5a with their superposed caliche paleosols having formed in subsequent stadial stages. The unconsolidated coastal sand dunes of Holocene age contain reworked Late Pleistocene skeletal carbonate sand based on AAR evidence. The most likely source of the reworked carbonate is from the erosion of the eolianites at Kaiehu Point. The Pleistocene eolianite-caliche paleosol sediments reveal variable Mg-content, stable isotope ratios and petrological characteristics consistent with changing degrees of weathering intensity and meteoric diagenesis. These changes are attributed to orographic effects resulting from relative sea-level changes. Accordingly, a two-phase model is favored for the formation of the eolianite-paleosol successions at Kaiehu Point, west Molokai. Eolianite sedimentation is initiated at times of marginally lower sea levels promoting the landward migration of bioclastic sand to form extensive eolian sandsheets. This is followed by a more pronounced phase of pedogenesis associated with a further fall in sea level and concomitant increased rainfall due to enhanced orographic effects.
Sp. Iss. 42947fu Times Cited:3 Cited References Count:50
Keywords: Amino acid racemization; aminostratigraphy; bermuda; carbonate lithofacies; cementation; cliche paleosols; eolianite; hawaii; island; Late Quaternary; limestone petrology; Marine; molokai; oahu; precipitation; sea level; sea-level; south-australia; Stable isotopes; stratigraphy